The Dilemma of Accountability for Professionals: A Challenge for Mainstream Management Theories - Mansouri, Maliheh (Journal of business ethics, 2014)
Professional institutions are increasingly confronted by fiscal constraints and political pressures to improve and increase their accountability in a competitive consumer-driven market. Accordingly, the need to ensure efficiency and accountability is of strategic importance. This article reports on a qualitative study of medical professionals that assessed the utility of financial incentives and external control methods derived from agency theory to ensure accountability of professionals. The authors argue that approaches derived from stewardship and institutional theories can extend the principal–agent perspective to sustain greater social and ethical accountability.